Can Electric Vehicles Deliver Energy and Carbon Reductions?. (May 2017) - Moriarty, Patrick; Wang, Stephen Jia
Abstract: Electric vehicles (EVs) are often thought to be an important means for reducing both the greenhouse gas emissions and energy consumption of global transport, particularly for road passenger transport. They are potentially more fuel efficient than comparable internal combustion engine vehicles (ICEVs), particularly in urban areas, because of regenerative braking. It is well-recognised that the energy efficiency of EVs decreases with the range the batteries must provide (because of rising battery mass), and that greenhouse gas comparisons with ICEVs depend on the grid electricity source. However, this paper argues that comparing EVs and ICEVs is much more complex than generally recognised. Uncertainties occur in both primary energy use and greenhouse gas emission calculations. Further, it may not be legitimate to evaluate these terms on a simple vehicle-km basis, because of spillover effects.